Land Regulation Following Independence in the Republic of Kazakhstan - JAXYBAYEV, Assanali (Journal of Advanced Research in Law and Economics, 2018)
Modern land regulation in Kazakhstan is the key factor ensuring the efficiency of socio-political and economic activity in Kazakhstan that supports and determines human culture and social structure in the state, production and rational utilization of its resource potential. Land regulation is performed by means of the relevant statutory acts – the Land Code of the Republic of Kazakhstan, laws and bylaws. The article presents the analysis of the staged development of land regulations in the Republic of Kazakhstan and the comparative analysis of land legislation of Kazakhstan and FSU countriesconducted by the historical and legal, and comparative and legal methods. The paper also defines prospects for applying advanced experience ofPRC land regulation in Kazakhstan.